Investigating the role of homologous recombination in the maintenance of chromosome stability - Graham, E (2023)
Homologous recombination (HR) is an essential DNA break repair pathway that maintains genome stability. BRCA2, PALB2, and RAD51 are key modulators of this pathway, mutations within which are associated with tumourigenesis. Centromeres are large repetitive DNA regions in the genome, defined through the presence of CENP-A. There is increasing evidence that centromeres experience instability across the cell cycle, impeding their function.